The Development of Paper Graph Media to Reduce Students’ Mathematical Dysgraphia - Amarulloh, Sandy Ihsan; Lestari, Puji; Yulianto, Eko (IKIP Siliwangi, 2026)
Students with mathematical dysgraphia frequently experience procedural errors in column-based arithmetic due to difficulties in visual–motor integration and spatial organization. These difficulties often result in misaligned digits, incorrect column placement, digit misreading, and improper regrouping, which are commonly categorized as Watson Errors. This study aims to develop Papergraph media as a visual structural learning medium to reduce mathematical errors in students with mathematical dysgraphia. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The media were developed based on a needs analysis focusing on students’ visual–motor characteristics and common procedural error patterns in arithmetic operations. Papergraph was designed as a grid-based medium to support accurate digit placement, place-value alignment, and vertical operational structure. The implementation of the developed media was evaluated using a Single Subject Research (SSR) design with an A–B–A pattern involving a fourth-grade elementary school student identified as having characteristics of mathematical dysgraphia. Data were collected through repeated measurement of arithmetic performance and analysis of Watson-type errors across baseline, intervention, and withdrawal phases.The results showed a significant reduction in mathematical errors during the intervention phase, particularly in digit misreading, column misplacement, incorrect digit combination, and regrouping errors. Performance improvements were maintained during the baseline-2 phase, indicating the internalization of spatial organization strategies facilitated by the Papergraph media. In conclusion, Papergraph demonstrates strong potential as an effective visual–structural learning medium to improve procedural accuracy and reduce Watson Errors in students with mathematical dysgraphia.